ANALISIS EFEKTIVITAS KEBIJAKAN PEMERINTAH DALAM MENINGKATKAN PENGGUNAAN ENERGI BARU DAN TERBARUKAN MENGGUNAKAN APROKSIMASI DATA DAN OPTIMASI DENGAN METODE SIMPLEKS - Suparman, Muhammad Nur Bintoro (Jurnal Ilmiah AdMathEdu, 2012)
This paper was prepared to analyze the effectiveness of government policies to increase the use of New and Renewable Energy (EBT) based on data obtained from the Pusat Data dan Informasi Energi Sumber Daya Mineral (Pusdatin ESDM). the rate of  EBT use in Indonesia is still low, recorded in 2010 remains at the 5% level. The Indonesian government seeks to encourage the increased use of renewable energy by at least 17% by 2025 (Presidential Decree No. 5/2006). By calculating the approximation of energy supply portion in  future based on the trends of energy supply portion changes  from year 2006-2010, it was concluded that the existing government policy now is not effective enough to increase new and renewable energy use as targeted by the government. from the approximation, it was calculated that supply of new and renewable energy in 2025 still amounted to 8.12% of the total energy supply. Through the optimization calculations using the simplex method, it was concluded that in order to achieve the target of new and renewable energy use by at least 17% by 2025, it would require the government policy to reduce the share of oil supply for a minimum of 1.989% per annum of the total energy supply as well as increasing the share of new and renewable energy supply a minimum of 0.903% per annum of the total energy supply. Addition and subtraction portion of each type of energy should not reduce the total supply of energy, because the national energy demand is increasing by years.   Key words: EBT, Pusdatin ESDM, the portion of energy supply, approximation, the simplex method.